Estudo do desgaste por erosão a quente de revestimento WC-Cr-Co - Silva, Luiz Rafael Resende da (2013)
This work studies the solid particle erosion behavior of WC-Co-Cr coatings, deposited by welding process PTAP (Plasma Transferred Arc Powder) and sintered blanket. These materials are used for covering components subject to erosive wear, since they are hard phase coatings with ductile matrix. Tests were performed in the gas blast erosion device available in the Laboratory TRICORRMAT (Tribology, Corrosion and Materials) at UFES (Universidade Federal do Espírito Santo), in three different conditions. In the first condition, the abrasive particle used was alumina, with an impact angle of 90° at room temperature. For the second and third conditions studied, test were performed at high temperature of 375 ºC with hematite as abrasive particle, and the variable evaluated was the angle of impact, consisting of 90 and 30. For all three conditions, the impact speed was 70 m/s and the flow of particles impacting the sample was 2 mg/mm².s. Tests were conducted to ASTM G 76. It was observed that the microstructure produced by the deposition process has a direct influence on the erosion resistance. For the first condition it was noted that all materials presented microcracks in the carbides and microcutting and micro ploughing in the binder phase. The micromechanisms observed in the case were due to the hardness of the alumina particles hardness. For the second and third conditions, in which hematite was used as erodent particle, there was a reduction on the number of microcracks in the carbides and the wear of the binder phase around the carbides was the main wear mechanism. For the third condition, as expected for low impact angles, it was observed that the carbides were pulled off by the wear of the binder phase in the direction of the particles impact. The coatings produced by the sintered blanket process showed a wear resistance four times greater than those obtained by PTAP. Samples and abrasive particles were characterized by scanning electron microscopy and quantitative analysis. Macro and micro hardness of the samples were also measured and related to the erosion behavior.